The Oxidative Stress of Human Sperm Cryopreservation - Steven D. Fleming; Laura K. Thomson (Antioxidants)
Due to their negligible cytoplasm and composition of the sperm plasmalemma, spermatozoa are particularly vulnerable to lipid peroxidative damage induced by reactive oxygen species (ROS). Most ROS are referred to as free radicals because they have unpaired electrons, causing them to scavenge electrons from atoms within tissues, resulting in oxidative damage to cellular components including cell membranes, intracellular organelles, and DNA. The potential consequences of oxidative stress include impaired sperm function, DNA fragmentation, and apoptosis. Understanding the mechanisms that mediate sperm damage during cryopreservation is key to the development of improved sperm freezing media formulations and methodology to mitigate its occurrence. Historically, elucidation of those mechanisms has proven largely elusive and is complicated by the positive role that ROS also play as messengers in redox signaling and the different pathways that mediate sperm DNA damage and apoptosis. More recently, oxidative stress has been revealed as the most likely suspect in cryopreservation-induced sperm DNA damage. This narrative review was intended to provide an in-depth analysis of the mechanisms involved and offer insight into possible improvements in sperm cryopreservation.